p-Type Quasi-Mono Silicon Solar Cell Fabricated by Ion Implantation - Chien-Ming Lee; Sheng-Po Chang; Shoou-Jinn Chang; Ching-In Wu (International Journal of Photoenergy)
The p-type quasi-mono wafer is a novel type of silicon material that is processed using a seed directional solidification technique. This material is a promising alternative to traditional high-cost Czochralski (CZ) and float-zone (FZ) material. Here, we evaluate the application of an advanced solar cell process featuring a novel method of ion implantation on p-type quasi-mono silicon wafer. The ion implantation process has simplified the normal industrial process flow by eliminating two process steps: the removal of phosphosilicate glass (PSG) and the junction isolation process that is required after the conventional thermal POCl3 diffusion process. Moreover, the good passivation performance of the ion implantation process improves Voc. Our results show that, after metallization and cofiring, an average cell efficiency of 18.55% can be achieved using 156 × 156 mm p-type quasi-mono silicon wafer. Furthermore, the absolute cell efficiency obtained using this method is 0.47% higher than that for the traditional POCl3 diffusion process.